Direct observation of three-electron collective decay in a resonant Auger process. (10th December 2015) - Eland, J H D; Squibb, R J; Mucke, M; Zagorodskikh, S; Linusson, P; Feifel, R
Abstract: Using a multi-electron coincidence technique combined with synchrotron radiation we demonstrate the real existence of the elusive three-electron collective process in resonant Auger decay of Kr. The three-electron process is about 40 times weaker than the competing two-electron processes.